2014
DOI: 10.1080/17441692.2014.953563
|View full text |Cite
|
Sign up to set email alerts
|

Participation in health planning in a decentralised health system: Experiences from facility governing committees in the Kongwa district of Tanzania

Abstract: Tanzania introduced the decentralisation of its health systems in the 1990s in order to provide opportunities for community participation in health planning. Health facility governing committees (HFGCs) were then established to provide room for communities to participate in the management of health service delivery. The objective of this study was to explore the challenges and benefits for the participation of HFGCs in health planning in a decentralised health system. Data were collected using semi-structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 17 publications
0
33
1
Order By: Relevance
“…We contributed to the conceptual understanding of representation by revealing that a mere presence of representative participatory organs and having individuals participating in the activities of these organs should be taken as a means rather than an end within itself. The findings challenge the assumption that the existence of decentralized community-and facility-level decisionmaking arrangements such as HFGCs would automatically improve youth representation and subsequently the accessibility of SRH services (Frumence et al 2014;Kilewo and Frumence (2015); URT 2001). It is worth learning that each community has a system of cultural norms through which policies are assigned meanings.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We contributed to the conceptual understanding of representation by revealing that a mere presence of representative participatory organs and having individuals participating in the activities of these organs should be taken as a means rather than an end within itself. The findings challenge the assumption that the existence of decentralized community-and facility-level decisionmaking arrangements such as HFGCs would automatically improve youth representation and subsequently the accessibility of SRH services (Frumence et al 2014;Kilewo and Frumence (2015); URT 2001). It is worth learning that each community has a system of cultural norms through which policies are assigned meanings.…”
Section: Discussionmentioning
confidence: 77%
“…As some of the previous studies have already revealed (Campero et al 2011;Frumence et al 2014;Damian 2018), effective representation of community voices and health concerns needs to entail at least three major dimensions. The first dimension is the physical presence of representatives of interested community groups in decision-making organs.…”
Section: Discussionmentioning
confidence: 99%
“…District resources were more limited in Uganda than those in Tanzania where pooled basket funding of approximately one USD per capita is made available to districts and can be spent on local priorities [40]. Improvement teams in Tanzania also tapped into other local resources available through the scale-up of community health funds and other insurance schemes [48], and this might have led to greater improvements in the availability of oxytocin, infection prevention items and supervision in Tanzania compared to those in Uganda. As drugs and supplies are crucial not just to provide quality care, but also to keep health workers motivated and increase community demand, this could be an additional factor.…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, decentralisation was initiated following the Ghana Health Service (GHS) and Teaching Hospital Act (Act 525) in 1996, which involved de-concentration of authority to the RHAs and DHAs in the country [ 6 , 7 ]. Benefits of decentralisation identified in various countries include higher regional and local authority, accountability, improved implementation of health care strategies based on need, greater efficiency, and increased responsiveness to community requirements [ 8 11 ]. However, health care decentralisation has also been associated with negative effects, such as the delayed transfer of funds from national government, lack of technical capacity of local governments, and inequity [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%